Temperament Dimensions and Awakening Cortisol Levels in Attention-Deficit/Hyperactivity Disorder - Carta, Alessandra; Vainieri, Isabella; Rommel, Anna-Sophie; Zuddas, Alessandro; Kuntsi, Jonna; Sotgiu, Stefano; Adamo, Nicoletta (Frontiers in Psychiatry, 2022)
Objective: To investigate whether the temperament dimensions Effortful Control (EC), Surgency-Extravertion (SE) and Negative Affectivity (NA) are associated with ADHD and how they relate to awakening cortisol levels, as a proxy measure of peripheral arousal. Methods: Parent-rated temperament and saliva samples were collected for 55 youths with ADHD, and 65 age-matched controls. Results: Relative to controls, youths with ADHD showed lower EC, higher NA and lower awakening cortisol levels, but did not differ in SE. A similar pattern of findings emerged in dimensional analyses linking temperament traits to inattention and hyperactivity-impulsivity symptoms. Results remained unchanged when controlling for the presence of co-occurring opposition-defiance and anxiety traits as well as medication status. Temperament dimensions were not associated with cortisol levels. Conclusions: Poor temperamental emotional and cognitive self-regulation show significant associations with ADHD, but do not appear to be linked to the under-arousal typically seen in ADHD.